The Representation Of Psychological Disorders In The Picture Of Dorian Gray By Oscar Wilde (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the representation of psychological disorders in The Picture of Dorian Gray. It aims to analyze key psychological dimensions of the protagonist, including narcissistic traits, moral corruption, and identity fragmentation. Using qualitative textual analysis, the study explores how aesthetic philosophy and the pursuit of eternal youth contribute to Dorian Gray’s psychological transformation. The findings suggest that his obsession with beauty results in progressive moral disengagement and the development of a divided self, symbolized through the contrast between his unchanging appearance and the deteriorating portrait. The study concludes that Wilde’s novel offers a profound psychological insight into the consequences of excessive desire and moral detachment